Accompaniment with the Sick: An Authentic Christian Vocation that Rejects the Fallacy of Prosperity Theology - Ramón Luzárraga (Journal of Moral Theology, 2019)
This article traces how prosperity theology is a corruption of a Calvinist idea describing the meaning and purpose of earthly prosperity, including good health, as a sign of God’s blessing. It has been secularized to the point where Americans often think that those who suffer are somehow ultimately, or exclusively, responsible for their situation in life. I then argue how this idea served as a catalyst for the dangerous idea of “positive thinking.” This idea implies, and sometimes makes explicit, that those who are suffering somehow deserve their situation and, therefore, must earn healing with faith in God expressed through the correct positive intellectual, emotional, and spiritual disposition. I conclude with a retrieval of the Latin American theology of accompaniment to refresh a Catholic understanding of suffering which can serve as a rebuttal to the negative influence of positive thinking and prosperity theology.